2015
DOI: 10.1002/eqe.2626
|View full text |Cite
|
Sign up to set email alerts
|

Shake table testing of un‐reinforced brick masonry building test model isolated by U‐FREI

Abstract: Summary This paper presents a detailed study on feasibility of un‐bonded fiber reinforced elastomeric isolator (U‐FREI) as an alternative to steel reinforced elastomeric isolator (SREI) for seismic isolation of un‐reinforced masonry buildings. Un‐reinforced masonry buildings are inherently vulnerable under seismic excitation, and U‐FREIs are used for seismic isolation of such buildings in the present study. Shake table testing of a base isolated two storey un‐reinforced masonry building model subjected to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In addition, the un-bonded application may increase the deformability capacity and damping ratio of the isolator [11]. A test on shaking table [12,13] showed that the FREI system can effectively reduce the top displacement and the acceleration response of an isolated structure, competing with the available commercial devices. A successive research [14], conducted by combining the recycled rubber isolation system with additional magnetorial damper, showed how the seismic performance of the isolated structure again severe earthquakes is improved significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the un-bonded application may increase the deformability capacity and damping ratio of the isolator [11]. A test on shaking table [12,13] showed that the FREI system can effectively reduce the top displacement and the acceleration response of an isolated structure, competing with the available commercial devices. A successive research [14], conducted by combining the recycled rubber isolation system with additional magnetorial damper, showed how the seismic performance of the isolated structure again severe earthquakes is improved significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al carried out the experimental study and 3D FE analysis of scaled U‐FREIs to investigate response under cyclic horizontal displacement in 0 ° and 45 ° directions. Das et al established effectiveness of model U‐FREI in seismic response control of two‐storey masonry test model by shake table testing.…”
Section: Introductionmentioning
confidence: 99%
“…From review of literature, it has been observed that most of the investigators carried out experimental and numerical studies on scaled models of FREIs with relatively low shape factors. There is little information for isolators with shape factors typical for seismic isolation, specifically 10 to 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This system can isolate the energy transmission of the earthquake from the foundation to the upperstructure. Some recent researches in the field employed glass fiber laminas to make the cost of the isolator even cheaper [4,5], sometimes in combination with used recycled rubber from tires or industrial waste [6,7], to further drop down costs.…”
Section: Introductionmentioning
confidence: 99%